2006
DOI: 10.1007/s10751-004-5649-y
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer Spectroscopy, NAA and PIXE Study on Some Archeological Problems of Ancient Chinese Ru Celadon

Abstract: By Mössbauer spectroscopy, NAA and optical spectroscopy, the coloring and the firing technology of ancient Ru celadon were studied. Also, the relationship between Ru Kuan celadon from Qingliang Temple and Ru celadon from Zhanggongxiang was studied by PIXE. The glaze color of Ru celadon depends on the ratio of the structural iron ions, i.e. the Fe 2+ /Fe 3+ ratio. Further, it depends on the firing conditions. As the Fe 2+ /Fe 3+ ratio gradually increases, the glaze color of Ru celadon will gradually change from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…청자의 비색은 태토와 유약 층이 고온의 환원 소성 과정 동안 물리화학적인 반응에 의해 유리질과 결정상을 형성하 게 됨으로 나타난다. 3,4) 유약은 장석, 석회석, 점토로 이루 어지며, 융제 역할을 하는 장석에 의해 유리질이 형성되는 데 이 과정에서 미량의 Fe 이온이 발색제 역할을 하여 청자 의 색도와 광택도에 영향을 준다. [5][6][7][8][9] 하지만 XPS와 같은 기 술로는 시편에 함유된 소량의 Fe에 대한 전자상태 변화를 관찰하는 것은 어렵다.…”
Section: 서 론unclassified
“…청자의 비색은 태토와 유약 층이 고온의 환원 소성 과정 동안 물리화학적인 반응에 의해 유리질과 결정상을 형성하 게 됨으로 나타난다. 3,4) 유약은 장석, 석회석, 점토로 이루 어지며, 융제 역할을 하는 장석에 의해 유리질이 형성되는 데 이 과정에서 미량의 Fe 이온이 발색제 역할을 하여 청자 의 색도와 광택도에 영향을 준다. [5][6][7][8][9] 하지만 XPS와 같은 기 술로는 시편에 함유된 소량의 Fe에 대한 전자상태 변화를 관찰하는 것은 어렵다.…”
Section: 서 론unclassified
“…From 1987 to 2000, Ru kiln site had been excavated for six times, the central production area of Ru Guan kiln had been found, yet the Guan kiln site of Northern Song dynasty remained undetermined and controversial even until now. 2,3 Until 2000, a kiln site was discovered in Zhanggongxiang, Ruzhou city, Henan province. Plentiful celadon products with exquisite workmanship and high quality were unearthed and their production age was considered between the late Northern Song dynasty and the early Yuan dynasty.…”
Section: Introductionmentioning
confidence: 99%
“…Since its firing period was short and the quantity of good Ru kiln products was limited, it had become the rare treasure. From 1987 to 2000, Ru kiln site had been excavated for six times, the central production area of Ru Guan kiln had been found, yet the Guan kiln site of Northern Song dynasty remained undetermined and controversial even until now 2,3 . Until 2000, a kiln site was discovered in Zhanggongxiang, Ruzhou city, Henan province.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a group of scientists in Shanghai Institute of Ceramics reported that the color is something to do with the iron content and light scattering of metastable two glassy phases in the glaze. 3 The details of the light scattering are used recently to interpret the iridescent effects synthesized from a short-range order in the amorphous photonic structures (APSs) by Zhang'…”
mentioning
confidence: 99%